2017
DOI: 10.3389/fimmu.2017.01763
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Potential MHC Class-II-Restricted Epitopes Derived from Leishmania donovani Antigens by Reverse Vaccinology and Evaluation of Their CD4+ T-Cell Responsiveness against Visceral Leishmaniasis

Abstract: Visceral leishmaniasis (VL) is one of the most neglected tropical diseases for which no vaccine exists. In spite of extensive efforts, no successful vaccine is available against this dreadful infectious disease. To support vaccine development, an immunoinformatics approach was applied to screen potential MHC class-II-restricted epitopes that can activate the immune cells. Initially, 37 epitopes derived from six stage-dependent, overexpressed antigens were predicted, which were presented by at least 26 diverse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
56
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 59 publications
(57 citation statements)
references
References 68 publications
1
56
0
Order By: Relevance
“…The previous report demonstrated that all the T-cell and B-cell epitopes might not evoke the immune cell appropriately. 1,6 Further reports also demonstrated the ability of specific T-cell epitopes to modulate the activation of Th1 and Th2 cells. 35,36 Importantly, in active VL cases, the IL-10 produced by Th2 cells decided the fate of the parasite inside the host.…”
Section: Discussionmentioning
confidence: 99%
“…The previous report demonstrated that all the T-cell and B-cell epitopes might not evoke the immune cell appropriately. 1,6 Further reports also demonstrated the ability of specific T-cell epitopes to modulate the activation of Th1 and Th2 cells. 35,36 Importantly, in active VL cases, the IL-10 produced by Th2 cells decided the fate of the parasite inside the host.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the in silico designed vaccines with epitopes derived from appropriate protein targets have the potential to progress toward advanced phases of vaccine development for visceral leishmaniasis. While the in silico studies by Khatoon et al [66] and Singh et al [67] largely utilized available genomic databases of L. donovani to select vaccine targets, Dikhit et al [11,70] performed thorough investigations involving in silico, in vitro and in vivo analysis to screen and validate immunogenic epitopes obtained from proteins that are increasingly expressed at the infective parasite stage. Such highly expressed proteins are likely important for physiological and/or infective process of the parasite and thus can be more effective vaccine targets.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to in vitro methods of epitope mapping such as phage display library, immunodominance and peptide competition assays, immunoinformatic mapping can be a powerful approach to facilitate screening of desired epitopes in immunogenic proteins [9]. Recent findings of leishmaniasis vaccine research also suggest that in silico predicted MHC class I and class II restricted epitopecontaining peptides derived from Leishmania antigens alone, as a cocktail, as a chimeric peptide or in combination with adjuvant can be substantially immunogenic in vitro and/or in vivo [10][11][12][13]. Thus, the application of immunoinformatics-based pipeline can facilitate largescale screening of peptide epitopes from Leishmania proteome for rational design of potent vaccines.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that the in silico designed vaccines with epitopes derived from appropriate protein targets have the potential to progress toward advanced phases of vaccine development for visceral leishmaniasis. While the in silico studies by Khatoon et al [104] and Singh et al [105] largely utilized available genomic databases of L. donovani to select vaccine targets, Dikhit et al [11,108] performed thorough investigations involving in silico, in vitro and in vivo analysis to screen and validate immunogenic epitopes obtained from proteins that are increasingly expressed at infective stage of parasite. Such highly expressed proteins are likely important for physiological and/or infective process of the parasite and thus can be more effective vaccine targets.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to in vitro methods of epitope mapping such as phage display library, immunodominance and peptide competition assays, immunoinformatic mapping can be a powerful approach to facilitate screening of desired epitopes in immunogenic proteins [9]. Recent studies on leishmaniasis vaccine research also suggest that in silico predicted MHC class I and class II restricted epitope containing peptides derived from Leishmania antigens alone, as a cocktail, as a chimeric peptide or in combination with adjuvant can be substantially immunogenic in vitro and/or in vivo [10][11][12][13]. Thus, the application of immunoinformatics-based pipeline can facilitate large scale screening of peptide epitopes from Leishmania proteome for rational design of potent vaccines.…”
Section: Introductionmentioning
confidence: 99%